What is Wrong with the Concept of Job Readiness in Higher Education? - Maltseva, Vera (Journal of Economic Sociology, 2021)
Equipping students with employability skills has become a novel mission of universities since the late 21st century. Discussion on how to make students more job-ready has appeared as a core of the education policy agenda. The roots of the job readiness agenda in higher education (HE) are mostly studied through the lens of changes in the HE sector and are regarded as a result of the massification and vocationalisation of HE. But these explanations only implicitly consider labor market changes that trigger the employability agenda. This paper challenges the job readiness agenda in HE, especially the pressure being put on HE institutions that are expected to fit students to employer’s needs. In order to find the grounds and justification for the employability agenda, I study its cornerstone theses through the lens of labor market theories. The research reveals that not all of these theses are well grounded in labor market theories and empirics. On the one hand, the employability narrative is justified by the decreased signaling function of education credentials and the increasing demand for universal skills and updated technical skills. On the other hand, alarmism concerning skill deficits and shortages that places pressure on HE doesn’t fully match theories and empirical evidence. The most relevant concept of employability and job readiness could be elaborated in the framework of universal competencies or 21st-century skills. Being job-ready means being prepared for a flexible career and lifelong learning instead of being fitted to short-term requirements. This conceptual framework establishes a shared responsibility for developing skills and managing skill gaps between individuals, employers and educational institutions.